Approximation of Signals (Functions) by Trigonometric Polynomials in Lp-Norm - M. L. Mittal; Mradul Veer Singh (International Journal of Mathematics and Mathematical Sciences)
Mittal and Rhoades (1999, 2000) and Mittal et al. (2011) have initiated a study of error estimates En(f) through trigonometric-Fourier approximation (tfa) for the situations in which the summability matrix T does not have monotone rows. In this paper, the first author continues the work in the direction for T to be a Np-matrix. We extend two theorems on summability matrix Np of Deger et al. (2012) where they have extended two theorems of Chandra (2002) using Cλ-method obtained by deleting a set of rows from Cesàro matrix C1. Our theorems also generalize two theorems of Leindler (2005) to Np-matrix which in turn generalize the result of Chandra (2002) and Quade (1937).